2008
DOI: 10.1007/s12291-008-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and disturbance in antioxidant balance in beta thalassemia major

Abstract: Repeated blood transfusion in beta thalassemia major patients may lead to peroxidative tissue injury by secondary iron overload. In the present study, 72 children with beta thalassemia major were included. Serum levels of total lipid peroxides, Iron, Total Iron Binding Capacity, Copper, Zinc, Vitamin E, plasma Total Antioxidant Capacity, activity of Erythrocyte Superoxide Dismutase, were measured. The findings were compared with 72 age matched healthy controls irrespective of sex. A significant increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 8 publications
7
68
1
Order By: Relevance
“…This is in agreement with Ghone et al, 24 who stated that, the majority of the beta thalassemia major patients had significant increase of serum iron with significant decrease of total iron binding capacity and have severe anemia due to ineffective erythropoiesis which is a primary reason for iron overload. Thus, increased iron may increase the potential of oxidative injury to erythrocyte and cell organelles.…”
supporting
confidence: 92%
“…This is in agreement with Ghone et al, 24 who stated that, the majority of the beta thalassemia major patients had significant increase of serum iron with significant decrease of total iron binding capacity and have severe anemia due to ineffective erythropoiesis which is a primary reason for iron overload. Thus, increased iron may increase the potential of oxidative injury to erythrocyte and cell organelles.…”
supporting
confidence: 92%
“…In patients with BTM, serum glycoprotein levels are lower, and desialylated serum glycoprotein quantities are higher than in controls [18]. Oxidative stress increases in both BTM and HBT [18,19,20]. Increased oxidative stress may disrupt the structure of the membrane glycoproteins on platelets and cause reduced platelet function [17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Their defense mechanism in biological system involves chain breaking and preventive mechanisms. 2,3 Same studies had shown that the erythrocytes of thalassemia patients are exposed to higher oxidative stress and a possible consequential accelerated apoptosis because of the high concentration of ROS. 4 ROS elimination involves glutathione transferase own, so these enzymes play an important physiological role.…”
Section: Introductionmentioning
confidence: 99%